Assessment of variations in reference evapotranspiration, yield and water use efficiency of mango under different fertigation regimes - ADAK, TARUN; KUMAR, KAILASH; SINGH, VINOD KUMAR (Journal of Soil and Water Conservation, 2021)
A field experiment was conducted during two consecutive mango growing seasons (2013-15) under subtropical climatic condition of Uttar Pradesh (Lucknow region). The study was carried out in a randomized block design with four treatments and five replications of different fertigation regimes applied at critical crop phenological stages of mango cv Dashehari. Lowest and highest mean monthly pan evaporation during the months from September to June ranged between 1.7 to 9.0 and 2.3 to 11.4 mm per day during 2013-14 and 2014-15 respectively. Estimated reference ET0 varied from 0.9 to 7.6 mm/day during the study period. Further, it was inferred that the cumulative reference ET0 was higher (45.6 to 594.5 mm/day) in the first season (May month i.e. fruit growth and developmental stages) as compared to 43.6 to 574.6 mm/day in 2014-15. The drip fertigation registered significantly higher fruit yield as compared to basin/untreated plot. The significantly higher fruit yield (72.6 kg/tree) was recorded under 75% RDF treatment followed by (62.3 kg/tree) under 50% RDF as compared to untreated one (45.4 kg/tree) during 2013-14 season. The increase in fruit yield over basin/untreated plot was 59.9, 37.2 and 15.2 per cent in 75, 50 and 25 per cent RDF respectively. The fruit yield during 2014-15 seasons was higher than 2013-14 with highest fruit yield of 118.4 kg/tree in treatment 75% RDF and 50% RDF and lowest as 101.8 kg/tree under untreated plot. These treatments also resulted significantly higher ascorbic acid content (29.76 to 36.56 mg/100g) in fruit pulp as compared to untreated plot (28.9 mg/100g), however, no significant effect on TSS and acidity of fruits was observed. Soil and leaf nutrients were not found deficient for fruit production during the study period. Water use efficiency was 7.09 to 11.34 and 15.9 to 18.5 kg fruits per m3 in 2013-14 and 2014-15 fruiting season respectively. Improvement in WUE of 10.8 to 27.7 per cent was observed in fertigated treatments as compared to basin/untreated application.